Archeo.FOSS XIV 2020 : open software, hardware, processes, data and format in archaeological research : proceedings of the 14th international conference 15-17 October 2020 - Bogdani, Julian,; Montalbano, Riccardo, 1985-; Rosati, Paolo, (Archaeopress Archaeology, 2021)
This volume represents the editorial outcome of the 14th edition of ArcheoFOSS international conference, which took place online between 15-17 October 2020. The event has been held annually since 2006 and is dedicated to the theoretical framework and actual application of free and open source software solutions and the promotion and encouragement of the Open Data paradigm for archaeology and, more generally, for Cultural Heritage. This volume represents the approach taken at the conference and the extensive participation it received, with 18 high-level and peer reviewed papers, well distributed in two thematic sections - application cases and development, and open data - contributed by more than 40 Italian and foreign scholars, researchers and freelance archaeologists working in the field of Cultural Heritage.